LIABILITY OF LEGAL PERSON IN INDONESIA: A STATUTORY AND PRACTICAL REVIEW - Dewi, Yetty Komalasari (UI Scholars Hub, 2013)
Liability of legal persons for criminal offences has been slowly, but making its way to the legislations of Indonesia. Trends of development indicate that the liability of legal persons for criminal offences has been regulated in few regulations and will be regulated in the bill of Indonesia Penal Code that is now being drafted. Grounds of liability of legal persons indicate that it is a question of a special from of criminal responsibility, adapted to legal persons.